Literasi Seloko Adat Masyarakat Kelurahan Sengeti - Irpina, Wiwin; W, Siti Asiah; Raudhoh, Raudhoh (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2019)
Introduction. This article aims to literacy of the indigenous community of Sengeti village in passing the indigenous values of Jambi Malay culture. The purpose of this research is to know how the community ability Sengeti Village in accessing, evaluating, and using and communicating information Tradition Seloko. Data Collection Method. The research method used in this research is descriptive in the form of a case study which aims to explain the literacy of the traditional seloko adat of the Sengeti Village community. The technique used in this research is qualitative, while the approach is in phenomenology Data Analysis. Qualitative analysis in communication research departs from a phenomenological approach, on the grounds that phenomenological analysis is more appropriately used to parse the problems of human subjects who are generally disobedient, changeable and so on. Result and Discussion. This result of research has depicted that; firstly, community ability Sengeti Village in accessing information this is optimally, it can be seen from the findings in the field that the community is able to define the information needs and understand the meaning of Tradition Seloko. Secondly, Then the ability to evaluate information not yet optimal can be seen from sub components of assessment and information settings, they rarely do information analysis, which is more dominant is done check and filter information. Thirdly, The community ability of Sengeti village to use and disseminate information could have been optimal. It can be seen they are using it as personal knowledge and spreading it as a frie nd and the person who is deemed to need information about Tradition Seloko. Conclusions. Activities to access information are carried out by participating in the traditional seloko training, asking people who know more about traditional seloko, looking for information on the internet. Information is evaluated by analyzing information, checking information, and filtering in search of the information needed. Information is used by applying the information obtained to life, making videos, articles, and YouTube vlogs that contain information about Seloko Adat for promotional needs and information sharing. From these activities, it is hoped that the community will be more careful in evaluating information and need the involvement of the younger generation to participate in preserving the traditional seloko.